EVALUASI RENCANA KERJA PEMERINTAH (RKP) 2017 PRIORITAS NASIONAL BIDANG PENDIDIKAN: Peningkatan Akses, Kualitas, Relevansi, dan Daya Saing Pendidikan - Yenni Anggrayni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2018)
Abstract Performance Evaluation of Government Work Plan (RKP) 2017 aims to find out the results of the achievement of development performance, especially the achievement of PN as material for the formulation and improvement of policies/ programs / activities, especially in the field of education with PN. Increasing Access, Quality, Relevance, and Competitiveness of Education achievement of development performance, especially the achievement of PN as material for formulation and improvement of policies / programs / activities, especially in the field of education with PN Improving Access, Quality, Relevance, and Educational Competitiveness. The research method used is gap analysis, namely performance measurement that compares the realization with a predetermined target, as well as an independent assessment of the implementing K / L. In general, National Priorities for Improving Access, Quality, Relevance and Competitiveness in Education show good achievements until 2017. Problems in implementing PN Increasing Access, Quality, Relevance, and Competitiveness Education can be categorized into three groups, namely institutional issues, budget, and HR. The follow-up was carried out, namely reallocating the budget, adjusting changes in the management authority of high schools and vocational schools, refocusing programs and activities, and optimizing HR utilization. Abstrak Evaluasi Kinerja Rencana Kerja Pemerintah (RKP) 2017 bertujuan untuk mengetahui hasil capaian kinerja pembangunan utamanya pencapaian PN sebagai bahan untuk perumusan dan perbaikan kebijakan/program/kegiatan khususnya di bidang pendidikan dengan PN Peningkatan Akses, Kualitas, Relevansi, dan Daya Saing Pendidikanmengetahui hasil capaian kinerja pembangunan utamanya pencapaian PN sebagai bahan untuk perumusan dan perbaikan kebijakan/program/kegiatan khususnya di bidang pendidikan dengan PN Peningkatan Akses, Kualitas, Relevansi, dan Daya Saing Pendidikan. Metode penelitian yang digunakan yaitu gap analysis yaitu pengukuran kinerja yang membandingkan antara realisasi dengan target yang telah ditetapkan, serta penilaian mandiri dari K/L pelaksana. Secara umum Prioritas Nasional Peningkatan Akses, Kualitas, Relevansi, dan Daya Saing Pendidikan menunjukkan pencapaian yang baik hingga tahun 2017. Permasalahan pelaksanaan PN Peningkatan Akses, Kualitas, Relevansi, dan Daya Saing Pendidikan dapat dikategorikan pada tiga kelompok, yaitu permasalahan kelembagaan, anggaran, dan SDM. Tindak lanjut yang dilakukan yaitu melakukan realokasi anggaran yang menyesuaikan perubahan kewenangan pengelolaan SMA dan SMK, melakukan refocusing program dan kegiatan, serta mengoptimalkan pendayagunaan SDM.